SATHI- An initiative for assuring quality seed supply to the farmers - Choudhary, Rakesh; Asati, Ruchi; Tiwari, J. K.; Singh, Yogeshwar; Chaturvedi, S. K. (Indian Farming, 2024)
Seed is a critical determinant of the agricultural productivity which decides performance and efficiency of other agri-inputs. Supply of quality seed of high-yielding varieties/hybrids certainly enhances crop productivity. With the objective of ensuring quality seed production and distribution chain, Department of Agriculture and Farmers' Welfare has designed the digital platform ‘SATHI- Seed Authentication, Traceability and Holistic Inventory’. SATHI provides information about every seed multiplication generation starting from nucleus seed production and lifting to multiplication in subsequent generation to the distribution of certified seed among farmers through registered dealers for the empowerment of the farmers. SATHI provides digital ecosystem to the seed sector that enhances the quality of the seed and provides single digital platform to all stakeholders like seed growers, seed processors, seed certification agencies and input dealers. Digital traceability of the seed through different modules of SATHI portal saves time significantly in seed growers’ registration, field inspection, generating reports, field inspection, reports on seed testing in laboratories and seed certification.